Production of eco-friendly lightweight fibrous concrete by replacing half of the sand with PET waste - Abbas O. Dawood; Zahraa A. Sabar (Advances in Civil and Architectural Engineering, 2025)
This experiment examined the properties of concrete with relatively high proportions of polyethylene terephthalate (PET) plastic waste used as a substitute for sand. In addition to the reference mixture, two percentages of PET shredded-plastic waste from discarded PET bottles were used as sand replacements: 30 and 50 %. To improve the performance of concrete mixtures with a high PET percentage, the concrete was also reinforced by adding polypropylene fibers at a rate of 1,5 % of the concrete-mix volume. Several concrete-mix characteristics were studied, such as workability, dry density, compressive strength, flexural strength, modulus of elasticity, absorption, and ultrasonic pulse velocity test. The use of plastic waste as a half replacement of fine aggregate in concrete has several benefits. One of which is the ability to produce lightweight concrete, where the dry density of concrete with a higher percentage of PET plastic waste of 50 % was 1912,30 kg/m3, and it had an acceptable compressive strength of approximately 25,3 MPa. The current study yielded important findings because recycling a high percentage of PET waste of half sand weight represents a structural advantage in reducing the weight of concrete. The proposed method also produces eco-friendly concrete due to the positive impact on the environment owing to the consumption of PET wastes within concrete mixtures.